National Center for Food Science and Technology linkage with the agri-food sector - Cortés-Muñoz, Marianela (2024)
The academia-socio-productive sector linkage model of the National Center for Food Science and Technology (CITA) is presented through examples of technology transfer in the agri-food field. This model is organized under three figures, technical assistance, technology transfer and licensing, and the CITA Co-Lab program. CITA has promoted the development of the agri-food sector by improving existing formulations, transferring new technologies and by bringing new products to the market. The CITA Technological Support Program for Industry (PATI) was created in 1984, while the CITA Co-Lab Program began its activities aimed at supporting entrepreneurs in 2020. Through the examples developed in this manuscript, it is possible to understand the processes and identify some factors that influence products’ successful entrance into the market.